Hierarchical Hollow Prussian Blue Rods Synthesized via Self‐Sacrifice Template as Cathode for High Performance Sodium Ion Battery. Issue 4 (14th September 2018) - Feng, Fan; Chen, Suli; Liao, Xiao‐Zhen; Ma, Zi‐Feng
Abstract: In this work, a facile strategy is proposed to synthesize hierarchical hollow rod‐like Mn‐doped Prussian blue (R‐PB) using MnO2 nanosheets as a self‐sacrifice template. The as prepared R‐PB with low contents of vacancies and coordinated water, and high content of sodium, exhibits appealing electrochemical performance as a cathode for sodium ion batteries (SIBs) achieving a high discharge capacity of 117.3 mAh g −1 and a capacity retention of 98.5% after 200 cycles at 1 C. Moreover, the specific capacity reaches 111.5 mAh g −1 at 5 C with a Coulombic efficiency (CE) of 93.8%. The high capacity, superior cycling stability, and enhanced kinetics of Na + migration of R‐PB are attributed to the positive effect of doped Mn ions and the hierarchical hollow rod‐like structure. The doped Mn ions in R‐PB activate the redox of Fe LS (C) in the high voltage region to reach a high capacity. The unique hierarchical hollow rod‐like structure provides a buffer space for the volume change during the insertion/extraction of sodium ions, enlarges the contact area between the electrode materials and electrolyte, and enhances the apparent diffusion coefficient of sodium ions in electrode materials. Abstract : A hierarchical hollow rod‐like Mn‐doping Prussian blue (R‐PB) is prepared via a facile MnO2 nanosheet self‐sacrifice template method. As a cathode for sodium ion batteries, R‐PB exhibits superior cycling stabilities and rate capabilities. The capacity retention is as high as 98% after 300 cycles at a high current of 5 C.